Analysis of Postoperative Outcomes in Unilateral Versus Bilateral DIEP Flap Reconstructions: A Single-Center Retrospective Study - Tekdogan, Boran; Martineau, Jérôme; Verbat, Miroslava; Dong, Edward T C; Correia, Daniel; Oranges, Carlo M (Journal of clinical medicine, 2025)
Background/Objectives: The DIEP flap is among the preferred techniques in autologous breast reconstruction due to better long-term outcomes, including higher satisfaction and more natural breast shape compared to implant-based breast reconstruction. With the rise in genetic testing, bilateral DIEP reconstructions are becoming more common, though they carry a higher risk of complications. This study aims to compare the risks between unilateral and bilateral procedures to improve surgical decision-making. Methods: A retrospective, single-center review was conducted on female patients who underwent DIEP flap breast reconstruction between January 2018 and May 2024. The study included patients with complete medical records and follow-up data, excluding those with incomplete records. Patient characteristics, operative details, and complications were thoroughly analyzed, with donor site complications assessed per patient and recipient site complications per breast. Results: During the study, 141 DIEP flaps were performed on 114 women, with 87 unilateral and 27 bilateral reconstructions. Age and BMI were similar between groups. However, chemotherapy was more common in the bilateral group (85% vs. 47%, p = 0.0011). Operative time was significantly longer in bilateral procedures (650 vs. 460 min, p < 0.0001). There were no statistically significant differences in recipient and donor site complications across groups. The hospital stay was significantly longer in the bilateral group (11 vs. 8.8 days, p = 0.024). Conclusions: Bilateral and unilateral DIEP flap breast reconstructions have similar complication and early take-back rates.